Effect of pilot fuel injection operating pressure in hydrogen blended compression ignition engine: An experimental analysis. (1st October 2015) - Quadri, Syed Azam Pasha; Masood, M.; Ravi Kumar, P.
Abstract: As the reduction of fossil fuel resources, environment threat, aggrandizement in energy demand and escalation in the cost of hydrocarbon fuels has caused interests in the evolution of alternative fuels for existing IC engines. Several researchers are promoting novel ideas and cutting edge technology which would eventually lead to leap fogging innovation and breakthrough in the area of alternative fuels. In this, concern hydrogen is increasing in demand because of its wide flammability limits, minimum ignition energy, high calorific value and high flame velocity. Apart from that it does not demand much modifications in the mechanism of the normal diesel engine to run as dual fuel and also it does not contain any carbon atom which eliminate emissions of CO2, unburnt and partially burnt hydrocarbons such as aldehydes and other greenhouse gases concerned with combustion. In the present experimental investigation 10% and 20% of hydrogen by mass of fuel is inducted into the combustion chamber in conjunction with air in hydrogen–diesel dual fuel mode. The variation in injection operating pressure is done to optimize the performance characteristics and emissions. Experimentations were conducted on three different injection operating pressures (IOP) i.e. 200, 220 and 240 bar at full load condition and the performance characteristics were calculated. The effect of IOP on emissions were measured and reported. The rate of heat release and pressure release were also measured.